Performance evolution in paralympic breaststroke swimmers - Daly, D.; Vanlandewijck, Y. (Biomechanics and Medicine in Swimming IX, 2003)
PURPOSE: The purpose of this paper is to track the evolution of Paralympic breaststroke performances from the 1996 Atlanta to the Sydney 2000 Paralympic Games. The fairness of using one selection procedure for all classes will be evaluated as well as the implications for the classification system in which the classes have been reduced from 10 to 9 in the last 4 years. METHODS: Paralympic end-race results were obtained for all Atlanta (71 men, 59 women) and Sydney (67 men, 61 women) 100 m breaststroke participants. Twenty four men and 21 women competed in this event in both Paralympics. Race analysis data was available for all Atlanta participants and Sydney finalists. World records (WR) were known for both periods in question and data on individual impairments was collected. Means, SDs and coefficients of variation (CV) were calculated. A point score for competitiveness, based on the class world record, was also given to performance. T-tests and ANOVA were used (p<.01). RESULTS: Women improved more than men. For men, in fact the winning times in 2 of the 6 classes competing was slower in Sydney than in Atlanta and the 1st place qualifying times hardly changed. The 8th place qualifying times did improve and the CV for the heats decreased between the two Games. For women, the gold medal times improved in all classes (3.5 % to 12.8 %). The 1st place qualifying time also improved between Atlanta and Sydney, while the 8th place times improved only sporadically. Over the period between the two Games, the women`s WRs improved by a mean of 4.5 %, (Max=8.4 %, SB9). One record did not change (SB6). In men, the mean improvement was only 1.69 % (Max=4.7 %, SB4) and 2 classes did not improve. Men`s class WRs were more in line with one another (RMSE = .029m/s vs .022m/s). For women, the records were more in line after Atlanta than after Sydney (RMSE=.017 m/s vs .021 m/s). Almost 60 % of the male gold and silver medalists in Sydney had also won a medal in Atlanta. In men, classes SB9, SB8 and SB4 were all significantly different from the other classes in swimming and turning speed. There were no differences in starting and finishing. In women, there were significant differences between classes in performance variables but classes SB7, SB6 and SB5 never differed from one another. The implication is that changes in the classification system may influence progress. Changes were in place more than 2.5 years beforehand. For some this may not have been soon enough nevertheless, to commit their training time entirely to breaststroke.